THE CONTRIBUTION OF CONSTRUCTIVIST GAMES (BLOCKS MEDIA) TO THE INCREASEMENT OF COGNITIVE ABILITIES - Rahmatunisa; Faisal Rachmat (CONS-IEDU, 2022)
This study used classroom action research. The aim of this study is to determine an increased ability of the children’s cognitive by playing blocks. The research subjects were children in group A & B Age 3-6 Years old of RA. Nurul Amiin, in a total of 23 children consisting of 9 Girls and 14 boys. Researchers used the method of action class research with observation and documentation to collect data. Analysis of the data used in this research is the analysis of descriptive and qualitative.The results showed an increased ability of the students cognitive at 90% based on the evaluation of the results on the first cycle and second cycle. It can be concluded that the implementation of learning by utilizing blocks media to improve children's cognitive abilities can be implemented in the learning process